2010
DOI: 10.1002/adma.201000980
|View full text |Cite
|
Sign up to set email alerts
|

A Color‐Tuneable Organic Light‐Emitting Transistor

Abstract: An organic light‐emitting field‐effect transistor whose emission color can be changed by the applied voltage is presented. The transistor is based on a parallel layer stack of acenes serving as organic transport and emission layers. During operation, the position of the recombination zone can be moved by a proper change in the drain and gate bias from one organic semiconductor of the stack to the other, inducing a change in the emission color from green to red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Thus low work function electrodes such as calcium, or multi-layer stacks involving organic materials cannot be easily used in the bottom contact geometry when solution processed active layers are employed. Another method involves an angled evaporation technique where either the substrate [9,20] or the sources inside the evaporator [21,22] are positioned at an angle. Optical lithography has also been used to form similar electrode structures [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus low work function electrodes such as calcium, or multi-layer stacks involving organic materials cannot be easily used in the bottom contact geometry when solution processed active layers are employed. Another method involves an angled evaporation technique where either the substrate [9,20] or the sources inside the evaporator [21,22] are positioned at an angle. Optical lithography has also been used to form similar electrode structures [23].…”
Section: Introductionmentioning
confidence: 99%
“…corresponds to an optical gap of 2.2 eV and 2.1 eV for DT-4F and DT-2F, respectively, which is essentially the same value as found for the unsubstituted DT (2.1 eV) [26].…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 56%
“…Moreover, in virtue of layered heterojunction structure and the spatial control of the recombination zone, ambipolar OLETs of color‐tunable emission could be obtained. A representative example was reported by Feldmeier and co‐workers, where two OSCs, tetracene and ditetracene, with different optical yet suited electrical properties were used to construct layered OLETs . It was found that when the external bias conditions were changed, the position of the recombination zone could be vertically moved from the metal/semiconductor interface to the semiconductor/dielectric interface accompanied by a change of the transport regime from unipolar to ambipolar.…”
Section: State‐of‐the‐art Strategies For High Performance Oletsmentioning
confidence: 99%
“…B) EL spectra, photographs of the recombination zone, and transistor schemes of such ditetracene and tetracene bilayer‐based OLETs under different bias conditions. Reproduced with permission . Copyright 2010, Wiley‐VCH.…”
Section: State‐of‐the‐art Strategies For High Performance Oletsmentioning
confidence: 99%